Pengaruh Perceived Quality Terhadap Customer Loyalty dengan Perceived Risk dan Customer Trust Sebagai Variabel Mediasi pada PT. XYZ - Edrick Heriyanto; Eko Harry Susanto (Universitas Tarumanagara, 2020)
The purpose of this study is to examine the influence of perceived quality toward customer loyalty which is mediated by perceived risk and customer trust for PT. XYZ that engaged in chemistry. There are four variables perceived quality as the independent variable, customer loyalty as the dependent variable, and perceived risk and customer trust as mediating variable. The sample was determined by purposive sampling method, the questionnaire was well-collected and was used in data processing using the Structural Equation Modeling (SEM) method with Smart PLS 3.0 program. This analysis was conducted on 115 respondents as customer of PT. XYZ. Based on the result of the study, it was found that perceived quality, perceived risk, and customer trust have influence towards customer loyalty, perceived quality have influence towards perceived risk and customer trust, perceived quality had an indirect effect on customer loyalty via perceived risk and customer trust.